Step
*
1
2
of Lemma
qmul_reverses_qle
1. a : ℚ
2. b : ℚ
3. c : ℚ
4. c < 0
5. 0 < -(c)
6. (c * b) ≤ (c * a)
⊢ a ≤ b
BY
{ (QMul ⌜-(c)⌝ (0)⋅ THEN QAdd ⌜a * c⌝ 0 ⋅ THEN QAdd ⌜b * c⌝ 0⋅)⋅ }
1
1. a : ℚ
2. b : ℚ
3. c : ℚ
4. c < 0
5. 0 < -(c)
6. (c * b) ≤ (c * a)
⊢ (b * c) ≤ (a * c)
Latex:
Latex:
1.  a  :  \mBbbQ{}
2.  b  :  \mBbbQ{}
3.  c  :  \mBbbQ{}
4.  c  <  0
5.  0  <  -(c)
6.  (c  *  b)  \mleq{}  (c  *  a)
\mvdash{}  a  \mleq{}  b
By
Latex:
(QMul  \mkleeneopen{}-(c)\mkleeneclose{}  (0)\mcdot{}  THEN  QAdd  \mkleeneopen{}a  *  c\mkleeneclose{}  0  \mcdot{}  THEN  QAdd  \mkleeneopen{}b  *  c\mkleeneclose{}  0\mcdot{})\mcdot{}
Home
Index